Interim Performance Progression (IPP) During Consecutive Season Best Performances of Talented Swimmers - Aylin K. Post; Ruud H. Koning; Inge K. Stoter; Chris Visscher; Marije T. Elferink-Gemser (Frontiers Media S.A., 2020)
Objective: The main goal of the present study was to investigate the interim performance progression (IPP) of talented swimmers. Part of this group ultimately made it to the top (referred to as elite swimmers) whereas others did not make it to the top (referred to as high-competitive swimmers). Rather than investigating performance progression based solely on season best performances, we included the first swim performance of the season in the metrics of IPP. Knowledge about the IPP of talented swimmers from and toward their season best performances relative to the first swim performance of the season will enhance our understanding of changes in season best performances during the talent trajectory and provide valuable insights for talent development and selection processes in competitive swimming.Methods: Fifteen thousand nine hundred and forty four swim performances (first swim performances of the season and season best performances) between 1993 and 2019 of 3,199 talented swimmers (of whom 556 reached elite level and 2,643 reached high-competitive level) were collected from Swimrankings and related to the prevailing world record of the corresponding sex. The pattern of IPP was represented by two phases: phase A and phase B. Phase A reflected the performance progression between the previous season best performance and the first swim performance of the current season (PPA) and phase B reflected the performance progression between the first swim performance of the current season and the season best performance of the current season (PPB). Depending on the normality check, we used independent sample t-tests or Mann Whitney tests to establish significant differences in PPA and PPB between elite and high competitive swimmers per age category per sex (p < 0.05).Results: Without denying individual differences, male elite swimmers improved more during phase B from age 15 till 24 compared to high-competitive swimmers (20.5% vs. 13.1%, respectively, p < 0.05). Female elite swimmers improved more during phase B from age 13 till 23 compared to high-competitive swimmers (21.1% vs. 14.6%, respectively, p < 0.05). Except for age 14 in males, there were no significant differences between performance groups in PPA.Conclusion: Talented swimmers who ultimately made it to the top (elite swimmers) are characterized with different patterns of IPP compared to talented swimmers who did not make it to the top (high-competitive swimmers). After puberty, elite and high-competitive swimmers performed in general ~1% slower at the start of their season compared to their previous season best performance (PPA). However, elite swimmers improved more in the period between their first swim performance of the season and their season best performance (PPB) from age 13 (females) and age 15 (males) onwards.